Isolation of Catechin and Catechin Glycoside from Indigofera welwitschii (Fabaceae) - Muntaka, A.; Sansi, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Proper phytochemical investigations of medicinal plants derived constituent has become of paramount importance owing to their versatile application as lead molecules in conventional medicine and as herbal medicine traditional practices. Indigofera welwitschii is not an exception. It belongs to genus Indigofera belongs and family fabaceae (Leguminaceae) that are well known for their ethnomedicinal claims and establish pharmacological activities. The aim of the study is to isolate and characterize phenolic compounds from the ethylacetate fraction of the methanol extract of Indigofera welwitschii. The preliminary phytochemical screenings of aerial parts (whole plant, leaves, flowers, seed and seedling) alone revealed the presence of different classes of compounds of which phenolic compounds are the most abundant. The method employed the use of silica gel chromatographic separation of the ethylacetate fraction using gradient elusion followed by repeated gel filtration using sephadex LH-20 to purify and obtain pure isolate; while the structure of the compound as was confirmed on the basis of chemical test, 1D- & 2D-NMR spectroscopy and comparison with an existing reported literature. catechin (a flavan-3-ol) and catechin glycoside were isolated. On the bases of literature search, this experimentation appears to be first report of isolation of epicatechin from the ethylacetate fraction of aqueous methanolic extract of the aerial parts of Indigofera welwitschii.